Optimization of Li2SnO3 Synthesis for Anode Material Application in Li-ion Batteries. (2017) - Musa, N.; Woo, H.J.; Teo, L.P.; Arof, A.K.
Abstract: In this work, Li2 SnO3 anode materials were synthesized successfully using sol-gel method. The synthesis was optimized by varying the preparation conditions (chelating agents: sucrose, oxalic acid or tartaric acid; pH value: 2, 5, 7 or 9 and calcination temperature: 600, 700 or 800 °C for fixed calcination time of 12 h). Li2 SnO3 synthesized using sucrose as the chelating agent at pH 5 with calcination temperature of 800 °C for 12 h produced the highest crystallinity with biggest crystallite size of Li2 SnO3 . Sucrose as the chelating agent has demonstrated superior chelating ability compared to both oxalic acid and tartaric acid. The chelation process has been analyzed and illustrated. pH 5 is the best pH environment as optimally available H + would accelerate the oxidation process of the chelating agent. Higher calcination temperature (800 °C) is needed to facilitate the crystal growth and generate more stable crystalline materials. The synthesized Li2 SnO3 was tested as anode material in Li-ion battery half-cell as a preliminary study. The electrochemical performance shows that it can be used in LIB application. Taking the low cost and simple sol-gel preparation method into consideration, this optimized synthesis route of Li2 SnO3 may pave way for future commercialization of low cost anode materials for LIBs.